Pengaruh model pembelajaran flipped classroom terhadap hasil belajar siswa - Antika Putri; Zaky Farid Luthfi; Maria Montessori; Rinia Zatalini (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
The low student learning achievement in Pancasila and Citizenship Education (PPKn), particularly the Pancasila Democracy System and Dynamics content, is the basis of this study. Traditional teaching methodologies and the lack of interactive components are contributing causes. The purpose of this study is to identify variations in student learning outcomes between the flipped classroom model group and the conventional method group. The experimental class and the control class were used as samples in this study, which used a quantitative design in the form of a quasi-experiment. Pretests and posttests were used for data collection, and paired and independent sample t-tests were used for data analysis. A significance value of 0.001 (<0.05) from the paired sample t-test indicates that learning success increased in both classes. In addition, the experimental class showed a greater increase in mean scores than the control class, indicating a significant difference between the two classes with a significance value of 0.091 (<0.10). Therefore, it can be concluded that the flipped classroom approach is more successful in improving student learning outcomes, which makes it a creative option for increasing student engagement and learning quality.